Characterization of Fibrillar Collagens and Extracellular Matrix of Glandular Benign Prostatic Hyperplasia Nodules - Bauman, Tyler M. (Public Library of Science, 2014)
OBJECTIVE: Recent studies have associated lower urinary tract symptoms (LUTS) in men with prostatic fibrosis, but a definitive link between collagen deposition and LUTS has yet to be demonstrated. The objective of this study was to evaluate ECM and collagen content within normal glandular prostate tissue and glandular BPH, and to evaluate the association of clinical parameters of LUTS with collagen content. METHODS: Fibrillar collagen and ECM content was assessed in normal prostate (48 patients) and glandular BPH nodules (24 patients) using Masson's trichrome stain and Picrosirius red stain. Second harmonic generation (SHG) imaging was used to evaluate collagen content. Additional BPH tissues (n = 47) were stained with Picrosirius red and the association between clinical parameters of BPH/LUTS and collagen content was assessed. RESULTS: ECM was similar in normal prostate and BPH (p = 0.44). Total collagen content between normal prostate and glandular BPH was similar (p = 0.27), but a significant increase in thicker collagen bundles was observed in BPH (p = 0.045). Using SHG imaging, collagen content in BPH (mean intensity = 62.52; SEM = 2.74) was significantly higher than in normal prostate (51.77±3.49; p = 0.02). Total collagen content was not associated with treatment with finasteride (p = 0.47) or α-blockers (p = 0.52), pre-TURP AUA symptom index (p = 0.90), prostate-specific antigen (p = 0.86), post-void residual (PVR; p = 0.32), prostate size (p = 0.21), or post-TURP PVR (p = 0.51). Collagen content was not associated with patient age in patients with BPH, however as men aged normal prostatic tissue had a decreased proportion of thick collagen bundles. CONCLUSIONS: The proportion of larger bundles of collagen, but not total collagen, is increased in BPH nodules, suggesting that these large fibers may play a role in BPH/LUTS. Total collagen content is independent of clinical parameters of BPH and LUTS. If fibrosis and overall ECM deposition are associated with BPH/LUTS, this relationship likely exists in regions of the prostate other than glandular hyperplasia.